2023
DOI: 10.1155/2023/2713614
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Injuries during Judo Tournaments

Abstract: Objective. To determine the injury incidence proportion, distribution of injuries by anatomical location; injury type; injury severity, time loss; mechanism and situations of injuries; and the relative risk of injuries by gender, age, and weight categories during judo tournaments. Study Design. It is a systematic review. Data Sources. A systematic review of the literature was conducted via searches in PubMed, EMBASE, Web of Science, CINAHL, SPORTDiscus, Google Scholar, and PEDro. Eligibility Criteria. All orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Notably, the 24–30 years old age group exhibited the lowest prevalence. In line with this, other studies have also found that older age groups tend to experience more injuries during judo practice 6 . Conversely, a study encompassing 21 competition seasons in France yielded the opposite results, indicating that younger age groups were more prone to sprains and fractures 28 .…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Notably, the 24–30 years old age group exhibited the lowest prevalence. In line with this, other studies have also found that older age groups tend to experience more injuries during judo practice 6 . Conversely, a study encompassing 21 competition seasons in France yielded the opposite results, indicating that younger age groups were more prone to sprains and fractures 28 .…”
Section: Discussionsupporting
confidence: 68%
“…Studies analyzing injuries during conventional judo competitions present similar anatomical locations, but with different orders of incidence. For instance, the knee, shoulder, and elbow were the most common injury sites during high-level judo competitions between 2005 and 2020 [26], whereas a systematic review by Mooren et al [6] found that the head is the most commonly reported site of injury in judo tournaments, followed by the hands, knees, elbows, and shoulders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst two studies addressed aspects related to one generation [53,55], one theoretical study [54] focused on general aspects that could be applied to both individuals and organisational bodies (e.g., federations). The majority of the studies [43,[50][51][52][53]56,57,61,63,64] included a high representation of male judoka (≈62%), whereas six reviews [54,55,[58][59][60]62] did not report this information. Only 2 studies [53,54] did not specify the athletic level of the considered judoka, and the remaining 14 reviews encompassed novice, recreational, amateur, and competitive (regional to world-class elite) athletes.…”
Section: Judo Practitioners Topics and Resultsmentioning
confidence: 99%